Preparation and Evaluation of Repaglinide Loaded Liposomes by Ether Injection Method (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Repaglinide is a commonly used antidiabetic drug to treat type 2 diabetes mellitus. However, it does not always support a suitable dose regimen due to its low bioavailability and half-life. The purpose of this study was to develop and analyze repaglinide loaded control release liposomes to provide suitable dosage form to treat diabetes. Repaglinide loaded liposomes were prepared by modified ether injection method. According to the USP-II paddle method, in vitro dissolution studies of liposomes were performed for 8 hours in phosphate buffer (pH 7.4). The stability study was executed according to ICH guidelines under three different environmental conditions for 14 days. Additionally, the presence and size of liposomal vesicles was confirmed by microscopic observation. The formulations containing phosphatidylcholine and cholesterol at a molar ratio of 1:0.4 revealed the highest drug entrapment efficiency of 73.1% with an optimum stirring rate of 300 RPM. The pegylated liposomes (PEG400/1500) prolonged the drug loading capacity for the formulations compared to non-pegylated liposomes. On the contrary, the addition of nigella oil caused a decrease in entrapment efficiencies of the liposomes. Most of the formulations followed zero order kinetic model and supper class II release mechanism. In vitro dissolution showed controlled release pattern of the liposomes and maximum drug release after 8 hours was 92.64%. Additionally, all the liposomal formulations were found to be more stable at refrigeration temperature (5 ± 2ºC) where pegylated liposomes were most stable over 14 days at three different environmental conditions. Visual observation under an optical microscope, the vesicular structure of liposomes was confirmed.Dhaka Univ. J. Pharm. Sci. 22(1): 89-96, 2023 (June)